PENYULUHAN KEBERSIHAN LINGKUNGAN UNTUK MENINGKATKAN KESADARAN LINGKUNGAN SISWA SEKOLAH DASAR - Yuliani; Asrul; Khaerunnizah; Tulsa’dia, Nurhalimah; Anisa; Thahir, Rahmatia; Magfirah, Nurul; Ernawati; Bahri, Aliem; Fadhilah, Nurul (Education and Talent Development Center of Indonesia, 2023)
Community service activities, namely environmental hygiene counseling aim to raise environmental awareness of elementary school students and provide information about waste management, to reduce environmental pollution by waste, especially plastic waste. This activity consisted of three stages, namely (1) material presentation, (2) ice breaking activities, and (3) poster submission. This activity was held on December 21, 2022 and is located at SD Inpres Bontomanai. The environment is a place where humans and other living things live that need to be kept clean and sustainable. Therefore extension activities are carried out to raise awareness to maintain environmental cleanliness from an early age.